Psychological Drivers of Tourists’ Storytelling for Sustainable Tourism: The Roles of Narcissism, Self-Esteem, Trust, and Reputation: A Case Study of National Park in Indonesia - Suhud, Usep; Chung, Sean B.; Allan, Mamoon; Hoo, Wong Chee; Azinuddin, Muaz; Sihotang, Doni Sugianto; Laphet, Jakkawat; Aujirapongpan, Somnuk (International Review of Management and Marketing, 2026)
The focus of this research was to find out the determinants of tourists in terms of their intention toward visiting the Tanjung Puting National Park, Indonesia. Item questions for the questionnaire were created using a nonprobability convenience sample technique, which yielded 230 samples of tourists. The collected data were analysed using exploratory factor analysis and structural equation modelling. The results show that narcissism is found significant to influence destination trust, self-esteem, and destination reputation as all the proposed hypotheses are accepted. Added to this, the destination trust and reputation and self-esteem should influence visit intention and the Willingness for storytelling. Visit intention is business related, and it should directly influence Willingness for storytelling. These results also bring practical implications for a better understanding of the marketing of destinations, consumer behaviour, and management of Tanjung Puting National Park to fully benefit from and promote its potential. The research also helps achieve the United Nations’ Sustainable Development Goals, particularly Goal 8: Decent Work and Economic Growth and Goal 12: Responsible Consumption and Production. These findings contribute to economic growth, based on an increase of destination reputation with sustainable tourism and ensuring that the natural resources are conserved alongside local community well-being.